Synthesis of 6-Deoxy-6-Amino Chitosan and applications thereof - Sayed, Shakeela (Department of Chemistry, 2022)
Chitin and chitosan play an important role in the context of a biorefinery, where waste is converted into useful products. The introduction of an amine onto chitosan at the C-6 position has led to the synthesis of a highly water soluble chitosan derivative, 6-deoxy-6-amino chitosan. However, all known synthetic methods for the synthesis of 6-deoxy-6-amino chitosan have some limitations, which acts as impediments to the scale up process. The introduction of an additional amine functionality allows for the further modification of the polymer, which can potentially enhance favourable properties such as solubility and biological activity. The solubility of the polymer in water is advantageous and opens up many different avenues of application. A shorter, greener and scalable synthetic pathway was sought due to the prior use of hazardous solvents and the generation of large quantities of waste. To aid the modification of chitin and chitosan, the solubility of these polymers was investigated using theoretical and computational modelling. Innovative synthetic means of introducing an amine at the C-6 position of the biopolymer was investigated. Ultimately, an expedient synthesis of 6-deoxy-6- amino chitosan was developed resulting in a much-improved yield and quality of 6-deoxy-6- amino chitin and chitosan. The improved 6-deoxy-6-amino chitosan was utilised in various applications such as antimicrobials, solid supported catalysts and electrospun nanofibers. 6-Deoxy-6-amino chitosan was co-spun with poly(ethylene oxide) and the resulting nanofibres were subsequently coated with silver nanoparticles which improved antimicrobial applications. Nanoparticles were produced using 6-deoxy-6-amino chitosan as the reducing and capping agent. The antimicrobial activity of these silver coated nanofibres was evaluated against E.coli and the antifungal activity of 6-deoxy-6-amino chitosan was studied against Fusarium verticillioides. Studies indicated that the 6-deoxy-6-amino chitosan and oligomers thereof exhibited an inhibitory effect on the growth of the fungus. Further work on the use of 6-deoxy-6-amino chitosan as an edible food coating in the treatment of strawberries was conducted. Initial results indicated that the onset of decay was delayed in the samples treated with the polymer. The previous successful application of recyclable 6-deoxy-6-amino chitosan as a water-soluble platinum group metal catalyst support was extended to a biomimetic pyridoxal 5′-phosphate (PLP) based support. Immobilised pyridoxal 5′-phosphate (PLP) was investigated as an enzyme mimic in the deamination of L-phenylalanine to phenylpyruvate.